2013
DOI: 10.4187/respcare.02357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Locally Applied Transforming Growth Factor Beta3 on Wound Healing and Stenosis Development in Tracheal Surgery

Abstract: BACKGROUND: Tracheal stenosis constitutes one of the most frequently seen problems in thoracic surgery. Although many treatment modalities to prevent fibroblast proliferation, angiogenesis, or inflammation that causes tracheal stenosis have been attempted, an effective method has not yet been found. In this study, a transforming growth factor beta3 (TGF-␤3)/chitosan combination was used for this purpose. METHODS: A slow-release preparation containing a thin layer of TGF-␤3 with a chitosan base was made. Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Tracheal stenosis is a pathological scar in which the inflammatory phase of cicatrization is prolonged and TGF- β 1 production and collagen synthesis and deposition in the ECM are increased [4, 7], which causes fibrosis at the lesion site [5, 6]. TSs are treated with endoscopic and surgical procedures combined with topical WHM application (e.g., MMC) to pharmacologically manipulate ECM formation and prevent tracheal restenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tracheal stenosis is a pathological scar in which the inflammatory phase of cicatrization is prolonged and TGF- β 1 production and collagen synthesis and deposition in the ECM are increased [4, 7], which causes fibrosis at the lesion site [5, 6]. TSs are treated with endoscopic and surgical procedures combined with topical WHM application (e.g., MMC) to pharmacologically manipulate ECM formation and prevent tracheal restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The following three isoforms of TGF- β have been described: TGF- β 1, TGF- β 2, and TGF- β 3; the first two isoforms (TGF- β 1 and TGF- β 2) are profibrogenic, whereas TGF- β 3 is anti-inflammatory and antifibrotic. The three isoforms are present in all wound-healing stages, particularly in the proliferative and remodeling phases [3, 5], and the therapeutic modulation of this factor may prevent fibrotic scarring [6]. …”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study reported a tissue reaction when using slow-release preparations containing TGF-b3 at a dose of 1 µg combined with chitosan. [12] This decreased the effectiveness of the film formations. Therefore, we used new preparations to ensure tissue compatibility.…”
Section: Discussionmentioning
confidence: 99%
“…When the defect exceeds these limits, it has been tried to replace the trachea using organic and artificial tubes that unfortunately causes severe complications such as infection, extrusion, obstruction, stenosis and chronic rejection [3]. Studies have suggested that the regeneration of the trachea through growth factors in platelet-rich plasma (PRP), such as platelet-derived growth factor (PDGF), and transforming growth factor-β (TGF-β), promotes tissue rejuvenation and tissue repair [4,5]. However, there are many obstacles to overcome, such as the rapid degradation of growth factors [6].…”
Section: Introductionmentioning
confidence: 99%